Kesesuaian Perubahan Penggunaan Tanah Tahun 2011-2019 Terhadap RTRW Di Kota Bogor - Prawira Danu Reja; Rakhmat Riyadi; Mrs Mujiati (Sekolah Tinggi Pertanahan Nasional, 2020)
The land use changes cannot be avoided in the development process. There are many conflict of interest between the utilization and the spatial planning document (called as RTRW) on it. This condition occurred in Bogor City. This study aims to determine the magnitude, distribution, and pattern of spatial changes, as well as its suitability to the RTRW. By using descriptive quantitative research methods, it is concluded that the rapid development that occurs in the city of Bogor does not have major implications for the mismatch level between land use and the RTRW of Bogor City. By using the descriptive quantitative research method, it is concluded that the rapid development that occurs in the Bogor City does not have major implications for the mismatch level between the land use utilization and the RTRW of Bogor City. This is indicated from: (1) the high rate of conversion on agricultural land to non-agricultural; (2) 43.57% of the Bogor City area is experienced changes in land use utilization; (3) the value on rate of change is 645,395 ha / year; (4) the growth pattern is concentric and along the way; and (5) 62.76% of the area shows compliance with the RTRW